2017
DOI: 10.1016/j.apjtm.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3-specific cytotoxic T lymphocytes induced by human leucocyte antigen-A*0201-restricted peptide effectively kill hepatocellular carcinoma cells in vitro

Abstract: The GPC3 522-530 peptide contains antigen-determinant and its specific CTLs can effectively kill HCC in a HLA-A2-restricted and peptide-dependent manner. Our findings suggest that this peptide may be valuable for development of therapeutic vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Then, we further confirmed that these candidate peptides had good binding power and stability to HLA-A2 molecules through T2 cell binding assay. While the T2 cell binding assay has been widely used in similar studies, 24 , 25 , 45 it should be noted that it does not directly confirm peptide-HLA stability. Therefore, we conduct several complementary assays to address this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we further confirmed that these candidate peptides had good binding power and stability to HLA-A2 molecules through T2 cell binding assay. While the T2 cell binding assay has been widely used in similar studies, 24 , 25 , 45 it should be noted that it does not directly confirm peptide-HLA stability. Therefore, we conduct several complementary assays to address this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that tumor-specific CTLs possess favorable cytotoxicity towards various types of cancer cell; in the presence of glypican-3 (GPC3), GPC3-specific CTLs diminish hepatocellular carcinoma cells ( 37 ), and melanoma-associated antigen 3 (MAGE-3)-specific CTLs inhibits the proliferation of bladder cancer cells and the growth of tumor xenografts in nude mice ( 38 ). Furthermore, mucin 1-specific CTLs show the potential to treat several cancer types, such as pancreatic cancer, melanoma, and colon cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%